GLOBAL PERSPECTIVES: EXPLORING INTERNATIONAL STUDENTS’ CULTURAL EXPERIENCES IN GRADUATE SEMINARS - Thompson, Emily Rose; Foster, David William (Ayden Journal of Management and Social Sciences, 2024)
This study delves into the immersive experiences of international graduate students hailing from China, Korea, and Taiwan while actively engaging in seminar discussions within the context of an American university in the southwest. Over a span of two months, data were meticulously gathered from three distinct graduate classes. Beyond linguistic proficiency, the research unearthed pivotal factors, notably goal orientation and one's sense of self within the classroom discourse, which emerged as significant themes embedded in the international students' encounters. The findings underscore the influential role played by classroom instructors and fellow students, who assumed mediating roles as these participants navigated their educational journey. Furthermore, these instructors and peers functioned as reflective mirrors, offering insights into the identities and roles of international students in the seminar classroom. This intricate interplay between participants and the educational environment paints a comprehensive picture of the dynamics at play in shaping the academic experiences of international graduate students.